2008
DOI: 10.1262/jrd.19148
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Insemination with Canine Spermatozoa Frozen in a Skim Milk/Glucose-Based Extender

Abstract: Abstract. Due to the recent outbreak of avian influenza, transportation of frozen canine semen with egg yolk has been sharply restricted. Thus, there is urgent need to develop a novel egg yolk-free extender for freezing canine spermatozoa. In the present study, the effect of using skim milk/glucose (SG)-based extender without egg yolk on the motility and fertilizing capacity of canine spermatozoa frozen-thawed in the presence of glycerol was examined. There was a tendency for the proportion of motile spermatoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Despite the fact that the dog is one of the most useful animals for various fields of research including reproduction [42][43][44], and successful cryopreservation canine embryo production in vitro is very limited, possibly because no optimal culture system for IVM of canine oocytes has yet been established. In order to clarify physiological evaluation of canine oocytes for IVM, we examined timedependent changes in MAPK and p34 cdc2 kinase activities during meiotic progression in canine oocytes, finding that both MAPK and p34 cdc2 kinase activities increased in a time-dependent manner and then reached maximal levels at 72 h of culture.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the dog is one of the most useful animals for various fields of research including reproduction [42][43][44], and successful cryopreservation canine embryo production in vitro is very limited, possibly because no optimal culture system for IVM of canine oocytes has yet been established. In order to clarify physiological evaluation of canine oocytes for IVM, we examined timedependent changes in MAPK and p34 cdc2 kinase activities during meiotic progression in canine oocytes, finding that both MAPK and p34 cdc2 kinase activities increased in a time-dependent manner and then reached maximal levels at 72 h of culture.…”
Section: Discussionmentioning
confidence: 99%
“…The collected semen was cryopreserved using the SM‐based extender described in the previous report with some modifications (Abe et al., ). To prepare the SM‐based extender, 30 mg/ml of skim milk (232100; Difco, Le Pont de Claix, France) and 119 mg/ml raffinose pentahydrate (R7630) were dissolved in Milli‐Q water at 60°C, and then, the solution was centrifuged at 10,000 g for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to EY, skim milk (SM) seems to be a suitable semen extender in canine species, because it is the most commonly used cryoprotectant for mouse (Nakagata, ) and goat spermatozoa (Dorado, Rodriguez, & Hidalgo, ). We previously reported that SM is an effective cryoprotectant for cryopreservation of canine spermatozoa (Abe et al., ). Motility and other motion parameters of canine spermatozoa frozen with a simple extender composed of SM, glucose and glycerol were equivalent or much better than the EY‐based extender.…”
Section: Introductionmentioning
confidence: 99%
“…Egg yolk the most common component used in canine semen extenders to protect spermatozoa from cold shock during chilled process (Mason, 2016). However, the presence of an avian influenza outbreak (Abe et al, 2008) and egg yolk affected by microbial contamination (Tarig et al, 2017) causes the desire to replace the egg yolk in extenders. Thus, it is necessary to develop extenders without use egg yolk.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%